2022
DOI: 10.3389/fmicb.2022.824217
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Within-Host and in vitro Genomic Variability and Sub-Genomic RNA Levels Indicate Differences in Viral Expression Between Clinical Cohorts and in vitro Culture

Abstract: BackgroundLow frequency intrahost single nucleotide variants (iSNVs) of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) have been increasingly recognised as predictive indicators of positive selection. Particularly as growing numbers of SARS-CoV-2 variants of interest (VOI) and concern (VOC) emerge. However, the dynamics of subgenomic RNA (sgRNA) expression and its impact on genomic diversity and infection outcome remain poorly understood. This study aims to investigate and quantify iSNVs and sgRN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Similar to the observations made from our previous study 14 and other works 19,35 , we were not able to detect any subgenomic Orf10. Among the eight screened subgenomic mRNAs, four were expressed in relatively higher abundance: Spike (S), M, Orf6, and Orf9 (N and any 3'-end open reading frames).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to the observations made from our previous study 14 and other works 19,35 , we were not able to detect any subgenomic Orf10. Among the eight screened subgenomic mRNAs, four were expressed in relatively higher abundance: Spike (S), M, Orf6, and Orf9 (N and any 3'-end open reading frames).…”
Section: Resultssupporting
confidence: 92%
“…That differed from other works which linked subgenomic RNA levels with active viral infection. A study reported for example decreased subgenomic RNA levels in severe cases 19 while others described a correlation between genomic and subgenomic RNA levels, which was being interpretated in these studies as a surrogate of viral activation and transcription [15][16][17][18] . In particular, the previously described apparent correlation between genomic and subgenomic Orf7 18 could be explained by the presence of subgenomic RNA roughly in the same proportion throughout the infection course synchronously with the presence of genomic RNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They detected, among 15,289 Sars-CoV-2 genomes analyzed, high frequency intra-host variability on codon 194, 215, 261, 655, 1254, 1258 and 1259 in spike domain, that represent a close region to our super variant codons and seems to be in similar distribution, close to key mutations E484, N501 per example. Agius et al identified kinds of high variables clouds near to the mean VOC mutations, considering a potential role of those variability strand in deep mutational process, linked with strong interactions with our immune system 27 . In their interesting works, intra-host variability was the most important in ORF1a domain and in spike domain as we found for spike and NSP3 domain.…”
Section: Discussionmentioning
confidence: 99%
“…RNA viruses tend to mutate at rates very close to this threshold [ 4 , 5 , 8 ] and replicate with relatively low fidelity compared to DNA viruses. As such, RNA viruses can diverge considerably even during a short infection [ 2 , 3 , 4 , 5 , 9 ] and generally exist in a host as a collection of genetically similar variants, termed quasispecies [ 10 , 11 ]. The ability of RNA viruses to diversify so rapidly represents a fitness advantage when infecting a biologically diverse host population [ 12 ].…”
Section: Viral Plasticity Is An Important Determinant Of Fitnessmentioning
confidence: 99%